Leadership and Management Skills Affecting Success in Business: A Case Study of Yala Small and Medium Enterprises - Nakruang, Dussadee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This descriptive study aimed to study and compare attributes, management skills, and leadership of entrepreneurs of Small or Medium enterprise in Yala Province and their success. This included examination of attributes, leadership, and management skills of entrepreneurs affecting their success in business. The sample targets of this study selected by proportional random sampling were 114 entrepreneurs of Yala Small and Medium enterprises. The questionnaire examined attributes. management skill, leadership and success in business. Data were collected by reliability-test, questionnaires and analyzed through descritive statistics (percentage, arithmetic mean and standard deviation) and inferenrial statistics (t-test, one way analysis of variance and multiple regressions). The results showed that most attributes are human skills and transformation leadership. There was no difference of success in business in aspects of gender, age year, education, position, and year of position. Transaction leadership, tranformation leadership and conceptual skill positively affected success in business at the high level. Putting these three factors together, they could predict success in business at 67.2 percent.